WEBSITE DESIGN OF UNITY YOUTH MASJID AL ISLAM MUNAWAROH CENGKARENG (PRIMAC) USING PHP, MACROMEDIA DREAMWEAVER MX 2004 AND MYSQL - Lingga Fitrianto; Rahayu Noveandini. Skom. MMSi Rahayu Noveandini. Skom. MMSi (Jurnal Sistem Informasi, 2007)
In scientific writing, the writer discussed about the design and manufacture of theIslamic Youth Association websites Masjid Al Munawaroh (PRIMAC) usingMacromedia Dreamweaver MX 2004.